Dose-dependency of theophylline clearance and protein binding. Issue 5 (May 1981) - Fleetham, J A; Bird, C E; Nakatsu, K; Wigle, R D; Munt, P W
Abstract : Dose-dependency in theophylline pharmacokinetics and protein binding characteristics was examined in 10 healthy male volunteers. Theophylline disposition was determined after an intravenous infusion of both 1 mg/kg and 6 mg/kg aminophylline in a randomised crossover study. There was considerable intrasubject variability in theophylline clearance but no significant dose-dependency. Theophylline protein binding was assessed by equilibrium dialysis at varying theophylline concentrations. The percentage of free non-protein bound theophylline was significantly increased at high theophylline concentrations. This increase in free theophylline would lead to a non-linear increase in the risk of toxicity with increasing drug concentration.